Nursing care for feeding and ventilation stoma: Literature review - Pires, Tarsila Reis Pinto; Siqueira, Milena Rangel; Ribeiro, Wanderson Alves; Grassel, Cristal dos Santos; Klein, Lorena Costa; Guedes, Miriam Maria Ferreira; Carneiro, Ana Fagundes; Constantino, Gabriel Nivaldo Brito; Santos, Daiane Lopes dos; Pedrosa, Pietro Henrique Benevides; Oliveira, Ane Raquel de; Souza, Viviane Cortes Cruz de; et al. (Brazilian Journal of Science, 2024)
Ostomy means the opening of an empty organ through the body. The term ostomy describes the surgical exteriorization of an organ, diverting its usual path. The difference between tracheostomy, gastrostomy, and jejunostomy has to do with the location of the opening. A tracheostomy is an artificial opening made by surgical means or percutaneous dilation in the anterior wall of the trachea performed in critically ill patients to clear the airways and allow gas to flow. Gastrostomy is an opening in the stomach, performed by a physician, in which a silicone tube or probe is placed that is externalized through the skin. Its purpose is to allow feeding and hydration for patients who cannot eat normally. Since the implementation of a gastrostomy imposes a new condition on the individual, and a need to adapt to the current situation, people in this condition may experience negative feelings and reduced levels of self-esteem. This is a descriptive, qualitative study of the reflective analysis type, a narrative review. Articles published in the last five years, in Portuguese, English, and Spanish, that addressed the topic were selected and analyzed to acquire greater depth and approximation with the object of study to support the reflections. Four categories were developed: Concepts and definitions of respiratory ostomy: Tracheostomy; Concepts and definitions of feeding ostomy: Gastrostomy; Concepts and definitions of feeding ostomy: Jejunostomy; Main nursing care with ventilation and feeding ostomies. Therefore, the study aims to reflect on nursing care with feeding and ventilation ostomy.